Contemporary Feminist Politics of Veganism: Carol J. Adams' The Sexual Politics of Meat and Alternative Approaches - Yilmaz, Ayce Feride (UNIV OTTAWA, DEPT COMMUNICATION, 2019)
Vegan ecofeminism growing out of ecofeminist ideas has been one of the first critical theories that explicitly politicized food and its cultural representations in terms of gender. As a diverse body of scholarship and activism, it has cogently demonstrated how meat has historically figured and continues to do so in interrelated oppressive structures, practices and meanings inscribed in diverse media. Nonetheless, ecofeminism in general, and vegan feminism in particular, have assumed an ambivalent trajectory ranging from prolific to dismissal as essential thinking. Feminist and critical media scholarship seem to have had its due share out of this dismissal of vegan feminism from broader critical theory as current feminist media research preserves its anthropocentric focus in dealing with diverse contemporary media phenomena. This paper attempts to reintroduce the theoretical and practical contributions of vegan ecofeminism for critical media scholars in an era of rapidly expanding digital landscapes and transnational media industries and growing global social inequalities and ecological destruction. The introductory part of this paper tries to make this paucity more clear within the landscape of feminist media research. This point leads to a brief revision of (vegan) ecofeminism's history and presentation of Carol Jay Adams' The Sexual Politics of Meat: A Feminist Vegetarian Critique as the epitome of the field illustrating intersections of oppressions around gender, species and other social categories forcing their way into dominant cultural imageries and media in terms of meat eating. Subsequent sections review the charged reception of (vegan) ecofeminist insights and their demise and comments on contemporary theoretical discussions on gender politics of veganism and related growing trends. Having forefronted the history of and current debates on vegan feminism in scholarship and research, the final part highlights some potential arenas of media research where this versatile body of knowledge problematizing intersecting social categories may be extended to compensate for its mainly anthropocentric focus.
Keywords: Vegan feminism; ecofeminism; feminist media studies; gender politics; VEGETARIANS; MEDIA; Communication